First record of the Pseudodiamesa branickii species group (Diptera: Chironomidae: Diamesinae) from central Mexico - Joanna Moreno; Julieta Massaferro; Margarita Caballero; Luis Oseguera (Revista Mexicana de Biodiversidad)
Larvae and pupae of the Pseudodiamesa branickii species group (Makarchenko and Makarchenko, 1999) (Diptera: Chironomidae) were found in 2 high-altitude lakes (El Sol and La Luna, 4,200 m asl), in the crater of the Nevado de Toluca volcano, in central Mexico. This is the first record of the genus in Mexico, and its southernmost report from a location that represents a transitional zone between the Nearctic and Neotropical regions. New information on the ecology and biogeographical distribution of the species group is given.